Cerebral venous thrombosis caused by spontaneous intracranial hypotension due to spontaneous spinal cerebrospinal fluid leakage in the high cervical region: a case report - Li, Man; Li, Yi; Tai, Liwen; Li, Hui; Wang, Li Qing; Zou, Yue Li; Feng, Wen Feng; Liu, Yue; Liu, Xiaopeng; He, Jun Ying (Frontiers in Neurology, 2023)
Spontaneous intracranial hypotension (SIH) may lead to cerebral venous thrombosis (CVT). This case report describes the diagnostic and treatment processes used for a patient with CVT caused by SIH due to spontaneous spinal cerebrospinal fluid (CSF) leakage in the high cervical region. Clinical data were collected from a 37-year-old man with an initial symptom of spontaneous posterior cervical pain. The diagnostic and treatment processes of SIH-induced CVT were described. A magnetic resonance imaging (MRI) study showed superior sagittal sinus thrombosis, and a lumbar puncture revealed a low initial CSF pressure of less than 60 mmH2O. The patient underwent anticoagulation and fluid rehydration therapies. No abnormalities were observed in the thoracic MRI scan, but a cervical MRI scan revealed a spontaneous CSF leak. An epidural blood patch with autologous blood was performed, and symptoms completely resolved 3 days after the procedure. This report proposes a diagnostic procedure for detecting rare cases of SIH-induced CVT, thereby preventing future misdiagnoses and delayed treatment. When a patient presenting with CVT in conjunction with intracranial hypotension has no history of trauma or piercing, SIH caused by spontaneous spinal CSF leakage should be considered as a potential cause of secondary low intracranial pressure. For detection of CSF leaks at rare sites, an MRI of the whole spine rather than a localized MRI of the spine needs to be performed to avoid misdiagnosis. An epidural blood patch should be performed as soon as possible as it may shorten the length of hospitalization and improve prognosis.